2016
DOI: 10.1038/onc.2016.213
|View full text |Cite
|
Sign up to set email alerts
|

PTPRO represses ERBB2-driven breast oncogenesis by dephosphorylation and endosomal internalization of ERBB2

Abstract: The plasma membrane-associated tyrosine phosphatase PTPRO is frequently transcriptionally repressed in cancers and signifies poor prognosis of breast cancer patients. In this study, deletion of Ptpro in MMTV-Erbb2 transgenic mice dramatically shortened the mammary tumor latency and accelerated tumor growth due to loss of Ptpro within the breast cancer cells but not in surrounding tissue as confirmed by hetero-transplantation studies. Both in vitro and in vivo data demonstrated that the phosphatase activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…As an integral membrane protein with its full isoform (PTPRO) expressed in many parenchymal cells (including lung, liver, and breast) and truncated isoform identified in inflammatory cells, such as macrophages and lymphocytes, PTPRO has been verified as a functional participator involved in the development of several tumors and inflammatory diseases [16-19]. Former studies suggested that PTPRO played critical roles in acute inflammation mediated by T lymphocytes [20] and macrophages [17] via activation of NF-kB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…As an integral membrane protein with its full isoform (PTPRO) expressed in many parenchymal cells (including lung, liver, and breast) and truncated isoform identified in inflammatory cells, such as macrophages and lymphocytes, PTPRO has been verified as a functional participator involved in the development of several tumors and inflammatory diseases [16-19]. Former studies suggested that PTPRO played critical roles in acute inflammation mediated by T lymphocytes [20] and macrophages [17] via activation of NF-kB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The cylindrical tumor cores were punched and transferred to the recipient block using a 2.0‐mm diameter precision punch. Blocks of the tissue microarray (TMA) were cut into 4‐μm sections and processed for IHC as described previously . TMA slides were incubated with anti‐NCOA1 antibody (sc‐8995, Santa Cruz) at room temperature for 1 hour followed by incubation with the HRP‐conjugated secondary antibody at room temperature for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Blocks of the tissue microarray (TMA) were cut into 4-μm sections and processed for IHC as described previously. [42][43][44][45] TMA slides were incubated with anti-NCOA1 antibody (sc-8995, Santa Cruz) at room temperature for 1 hour followed by incubation with the HRP-conjugated secondary antibody at room temperature for 30 minutes. Immunostaining was visualized by 3, 3′-diaminobenzidine (DAB), and the cell nuclei were counterstained by hematoxylin.…”
Section: Tissue Microarray Array (Tma) and Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the present study, we observed that AC104135.3 was co‐expressed with the well‐known oncogene ERBB2 . ERBB2 overexpression occurs in approximately 30% of breast cancer patients and promotes the proliferation or/and metastasis of breast cancer cells through cross‐talk with multiple oncogenic pathways . Interestingly, in the stratification analysis, we observed that the protective effect of rs11471161 in breast cancer was significant in ERBB2‐negative status (Table ).…”
Section: Discussionmentioning
confidence: 83%